PENGARUH DAYA SAING, BUDAYA KEUANGAN, DAN KEPUTUSAN PEMBAYARAN KREDIT TERHADAP AKSES KEUANGAN - Soedarwati, Ernie; Arifiani, Rahmawaty (Berajah Journal, 2024)
The background to the problem in this research is that access to finance is still an obstacle for SMEs to grow. Seeing this condition, the OJK has established regulations related to online financing for SMEs (equity crowdfunding) which is currently booming in the financial world. This research aims to determine the influence of competitiveness, financial culture, and credit payment decisions on financial access. This research uses a quantitative approach. The research results show that access to financial services is an important feature in SME business operations. Different from large companies, SMEs show personalization because their development depends on entrepreneurs who are also owners and founders. This personalization effect causes banks to doubt their behavior in repayment of credit taken. The results of this research show that SMEs' access to finance is influenced by competitiveness factors, financial culture, and credit payment decisions. These findings provide literacy in the financial sector related to SMEs' accessibility to financing and credit payment decisions, competitiveness, and financial culture. It can be concluded that capacity (competitiveness and culture) and willingness (decision) to repay loans determine the accessibility of SMEs to financing. However, on the other hand, SMEs still complain about the difficulty of their access to financing in conventional financial institutions. In fact, this injection of external funds can be used by SMEs to develop their businesses and expand their markets.